Analisis bibliometrik perkembangan potensi energi baru dan terbarukan di Indonesia menggunakan R Biblioshiny dan VosViewer - Tupan, Tupan (Daluang: Journal of Library and Information Science, 2022)
Introduction. Indonesia is one of the countries that has the highest potential for clean and renewable energy in the world. Indonesia's renewable energy potential includes geothermal, hydro and micro-mini hydro, bioenergy, solar, wind and ocean waves. To find out this potential, a bibliometric analysis was carried out on the development of new and renewable energy potential in Indonesia.Methodology. Data on the development of new and renewable energy potential is taken from the Scopus database. Data retrieval was carried out through a search with the keyword criteria used were renewable energy OR potential of new renewable energy OR implementation of new renewable energy OR geothermal OR biofuel OR biogas OR biomass OR solar panels AND Indonesia earth radiation OR. The analysis of this study uses R bibliophagy and Vos Viewer.Results and discussion. The results show that the highest annual publication trend will occur in 2021. The largest number of citations for new and renewable energy publications in Indonesia is Biodiversity with a total of 74 publications and 250 citations. The Journal of the Meteorological Society of Japan is a widely used publication source for publish research results on new and renewable energy. Pambudi, N.A. is a researcher who conducts the most research on geothermal energy (geothermal). Keywords that are often used are biomass, geothermal, biogas, biodiesel and biofuel.Conclusion. It was concluded that biomass, geothermal systems, renewable energy, alternative energy and energy policy were the most studied topics.